Solvable Nuclear War Models - Dalkey, Norman C. (Management Science, 1965)
This paper deals with an aggregated, two-sided war game, one of several designed to study the use of abstract models for strategic planning. A payoff function for the war game is defined making use of an assumption of increasing concern as a critical level of damage is approached. A very simple, one-weapon version of the central nuclear war game has an analytic solution, indicating the existence of a stable (equilibrium) point in pure strategies if each side has a nonnegligible counterforce capability.